Growth and diffusion dynamics of tractor in Punjab - SHEKHAWAT, RAVINDRA SINGH; SINGH, K N; BHATTARAI, MADHUSUDAN; GURUNG, BISHAL; LAMA, ACHAL; SARKAR, KRISHNA PADA; DONI, RIPI (The Indian Journal of Agricultural Sciences, 2019)
Over the last few decades, India has seen an incessant increase of tractor use as well as expansion in its domestic tractor manufacturing industry, in spite of comparatively slow wage growth and a slow decline in the employment share of the agricultural sector. If the present situation is to be accounted, arguably as much as 90% of the country’s farm area may be prepared by tractors. Monomolecular nonlinear growth model methodology was applied to Punjab’s tractor density time-series data to capture the diffusion of tractor. Levenberg-Marquardt iterative method was applied with the help of SAS by using PROC NLIN statement and the obtained results show that the model is a good fit for the data under consideration. Further, Compound annual growth rate (CAGR) of tractor density was also calculated to infer about the changes in tractor density over the time (1982–2015 ) and found that CAGR was high during 80s and 90s than 2000s. Despite of low growth in last decade, Punjab is expected to have more adopters of tractor in coming years. From this empirical study, we also infer that 90 per cent tractor penetration will be achieved by 2032 in Punjab.